Answer:
x = -3 or x = -2
Explanation:
Our equation is:
.
We see that all three terms are multiples of 3, so let's just divide both sides by 3 to simplify:
. We now have:
.
To factor this, we want to look at the pairs of factors of the constant 6 and see which pair will add up to 5 (from the 5x). After some searching, we can easily see that 3 * 2 = 6 and 3 + 2 = 5, so this is the pair we're looking for. Then, we factor:
.
Finally, to solve, we know that if x + 3 = 0 or if x + 2 = 0, then the product will be 0, so: x + 3 = 0 --> x = -3 OR x + 2 = 0 --> x = -2
Thus, the answer is: x = -3 or x = -2.
Hope this helps!